27 Exosomes Released from Endothelial Cells are Cardioprotective. (19th January 2014) - Zheng, Y; Vicencio, J M; Yellon, D M; Davidson, S M
Abstract : Ischaemic preconditioning attenuates ischaemia-reperfusion (IR) injury, however, the mechanism is not fully understood. Cardiac endothelium can communicate with the underlying myocardium and regulate its activity. Cells can communicate via exosomes – small, secreted, vesicles which carry proteins and miRNAs. The aim of this study was to characterise exosomes released from endothelial cells, determine whether they can protect against simulated IR injury and whether they are involved in preconditioning. Co-culture of cardiomyocytes with normoxic HUVEC cells prior to in vitro simulated IR reduced the percentage of cell death from 80 ± 11% to 51 ± 4% (P < 0.05; n = 3) respectively indicating a diffusible factor from endothelial cells can confer protection in cardiomyocytes. Exosomes were purified from HUVEC using differential centrifugation and characterised by Nanoparticle Tracking Analysis, electron microscopy, and flow cytometry. Pre-incubation of cardiomyocytes with HUVEC exosomes before simulated IR reduced the percentage of cell death from 88 ± 4% to 55 ± 3% (P < 0.05; n = 3). Interestingly, preconditioning of HUVEC cells by exposure to 30 min simulated IR increased exosomes release ~2 fold. Incubation of cardiomyocytes with exosomes from preconditioned HUVEC further reduced cell death to 45 ± 10% (P < 0.05 vs control; NS vs normoxic exosomes; n = 3). This preliminary data indicates a trend towards increased protection with exosomes from preconditioned cells which is now under further investigation. This is the first data showing that endothelial exosomes can stimulate resistance to simulated IR in cardiomyocytes.